A Biopsychosocial and Interprofessional Approach to the Treatment of Family and Intimate Partner Violence: It Takes a Village - Poleshuck, Ellen; Wittink, Marsha N.; Crean, Hugh; Juskiewicz, Iwona; ReQua, Michelle A.; Cerulli, Catherine (Frontiers in Psychiatry, 2021)
Family and intimate partner violence and abuse (FIPV) is a critical public health problem with repercussions for mental and physical health. FIPV exposure also is associated with social difficulties such as low socioeconomic status, legal issues, poor access to employment and education, housing instability, and difficulty meeting other basic needs. As a biopsychosocial problem, one discipline alone cannot adequately address FIPV. While individuals who experience FIPV traditionally seek respite, care and safety through domestic violence shelters, social services or courts, they also often present to health care settings. Building on the medical-legal partnership model with critical input from a community advisory board of individuals with lived experiences of FIPV, we implemented a person-centered approach in the health care context to cohesively integrate legal, safety, social, psychological and physical health needs and concerns. The purpose of this paper is to describe the Healing through Health, Education, Advocacy and Law (HEAL) Collaborative for individuals who have experienced psychological abuse, physical abuse, sexual abuse, or neglect related to child maltreatment, intimate partner violence, and/or elder abuse, and review our real-world challenges and successes. We describe our interprofessional team collaboration and our pragmatic biopsychosocial framework for bringing together: professional and stakeholder perspectives; psychological, medical, legal, and personal perspectives; and clinical, evidence-based, and educational perspectives. There is no doubt that creating a program with biopsychosocial components like HEAL requires professionals appreciating each other’s contributions and the need to begin working from a common goal. Furthermore, such a program could not be successful without the contributions of individuals with the lived experience we seek to treat, coupled with the external health care clinicians’ input. We describe lessons learned to date in an effort to ease the burden for those seeking to implement such a program. Lessons include HEAL’s more recent clinical adaptions to serve patients both in-person and via telehealth in the wake of COVID-19.